The Topicality and the Utility of the Teachings of the Holy Fathers - Liviu Petcu (Anastasis: Research in Medieval Culture and Art)
The Holy Fathers, “great scholars and teachers”, are considered as the normative representatives of the doctrinarian tradition of the Church, as especially authorized witnesses of faith. They led a holy life and also distinguished themselves through the fact that they preached the teachings received from the Saviour and the Holy Apostles.They are not only the representatives of the doctrinarian tradition of the Church, but also the witnesses and criteria of true faith, the judges of Orthodoxy – this feature has not only a historic value and dimension, but also atemporal and generally spiritual ones. The Holy Fathers are extremely “contemporary”, as they reach directly the Christians in our times and provide answers to the essential questions of mankind. By studying the patristic literature, we acquire the way of thinking of the saints, which is helpful at anytime and in any circumstance and allows us to show our faith and answer topical issues as they themselves would have done if they were still alive now. By a careful and pious reading of the works of the Holy Fathers, contemporary human beings may find the solutions to their problems and thean swers to their questions, as they are models of Christian living, wisdom and simplicity, and their theological knowledge and the truths they preached were un animously accepted and admired by the whole Church.